Epigenetic modification regulates the ligamentum flavum hypertrophy through miR-335-3p/SERPINE2/β-catenin signaling pathway - Yongzhao Zhao; Shuai Jiang; Longting Chen; Qian Xiang; Jialiang Lin; Weishi Li (Cellular & Molecular Biology Letters)
Abstract Background Epigenetic modifications have been proved to play important roles in the spinal degenerative diseases. As a type of noncoding RNA, the microRNA (miRNA) is a vital class of regulatory factor in the epigenetic modifications, while the role of miRNAs in the regulation of epigenetic modifications in ligamentum flavum hypertrophy (LFH) has not been fully investigated. Methods The miRNA sequencing analysis was used to explore the change of miRNA expression during the fibrosis of ligamentum flavum (LF) cells caused by the TGF-β1 (10 ng/ml). The downregulated miRNA miR-335-3p was selected to investigate its effects on the fibrosis of LF cells and explored the accurate relevant mechanisms. Results A total of 21 miRNAs were differently expressed during the fibrosis of LF cells. The downregulated miR-335-3p was selected for further investigation. MiR-335-3p was distinctly downregulated in the LFH tissues compared to non-LFH tissues. Overexpression of miR-335-3p could inhibit the fibrosis of LF cells. Further research showed miR-335-3p prevented the fibrosis of LF cells via binding to the 3′-UTR of SERPINE2 to reduce the expression of SERPINE2. The increased SERPINE2 expression might promote the fibrosis of LF cells via the activation of β-catenin signaling pathway to promote the transcription of fibrosis-related genes (ACTA2 and COL3A1). Conclusions Our results revealed that miR-335-3p prevented the fibrosis of LF cells via the epigenetic regulation of SERPINE2/β-catenin signaling pathway. The epigenetic regulator miR-335-3p might be a promising potential target for the treatment of LFH. Graphical Abstract